OBSERVATIONS ON THE INDIAN SHORT-FJNNED EEL ANGUILLA BICOLOR BICOLOR McCLELLAND CAUGHT FOR THE FIRST TIME AT SEA DURING SPAWNING MIGRATION - Dorairaj, K; Nandakumar, G (Indian Journal of Fisheries, 2011)
One migrant Indian short-finned female silver-eel, Anguilla bicolor bicolor McClelland, measuring 866 mm in total length and 1150 g in weight, caught alive for the first time from the inshore area off Karwar in July 1980, is recorded. Salient morphological, morphometric and gonadal characteristics of the migrant eel, compared with those of non-migrant and partially spawned female eels, confirmed that the eel was in a maturing stage and was on its way to oceanic spawning ground.